Abused by the Patriarchy: Male Victims, Masculinity, "Honor"-Based Abuse and Forced Marriages - Idriss, Mohammad Mazher (Journal of interpersonal violence, 2022)
The causes and effects of what is often referred to as ?honor?-based violence/abuse (HBV/A) and forced marriages on men and boys is an under-researched field of patriarchal violence. This lack of research has resulted in an imperfect understanding of how and why men become victims of HBV/A and an absence of an effective theoretical framework in which to analyze their experiences. Through an examination of 29 Case Files obtained through a gender-neutral domestic abuse refuge charity in the East Midlands, the United Kingdom, this original research will explore the ways that men, particularly younger males and those who do not conform to cultural norms of masculinity, are harmed by patriarchal structures. In doing so, this article brings to light new data and adds to the patriarchal framework for understanding HBV/A and why it is committed against men. The results of this study reveal that the ways in which HBV/A and forced marriages were presented in the Case Files present both analogies to and distinctions with the infliction of Violence Against Women and Girls (VAWG) in similar circumstances. This discovery is important for several reasons: (a) it demonstrates that men and boys are harmed by patriarchy and that patriarchal theories of violence must therefore evolve to better recognize groups of male victims; (b) it provides a typological framework to identify the different types of male victims, the types of abuse and the perpetrators involved, including the involvement of mothers as primary and secondary perpetrators; and (c) that male victims require appropriate intervention and must be taken seriously by state agencies if men are to come forward and disclose abuse.